Histological Analysis and Gene Expression of Satellite Cell Markers in the Pectoralis Major Muscle in Broiler Lines Divergently Selected for Percent 4-Day Breast Yield - Orlowski, Sara K.; Dridi, Sami; Greene, Elizabeth S.; Coy, Cynthia S.; Velleman, Sandra G.; Anthony, Nicholas B. (Frontiers in Physiology, 2021)
Muscle development during embryonic and early post-hatch growth is primarily through hyperplastic growth and accumulation of nuclei through satellite cell contribution. Post-hatch, muscle development transitions from hyperplasia to hypertrophic growth of muscle fibers. Commercial selection for breast yield traditionally occurs at ages targeting hypertrophic rather than hyperplastic growth. This has resulted in the production of giant fibers and concomitant challenges with regard to muscle myopathies. The current study investigates the impact of selection during the period of hyperplastic growth. It is hypothesized that selection for percentage breast yield during hyperplasia will result in an increased number of muscle cells at hatch and potentially impact muscle fiber characteristics at processing. This study characterizes the breast muscle histology of three broiler lines at various ages in the growth period. The lines include a random bred control (RAN) as well as lines which have been selected from RAN for high (HBY4) and low (LBY4) percentage 4-day breast yield. Post-rigor pectoralis major samples from 6 males and 6 females of each line and age were collected and stored in formalin. The sample ages included embryonic day 18 (E18), post hatch d4, and d56. The samples were processed using a Leica tissue processor, embedded in paraffin wax, sectioned, and placed on slides. Slides were stained using hematoxylin and eosin. E18 and d4 post-hatch analysis showed advanced muscle fiber formation for HBY4 and immature muscle development for LBY4 as compared to RAN. Post-hatch d56 samples were analyzed for fiber number, fiber diameter, endomysium and perimysium spacing. Line HBY4 had the largest muscle fiber diameter (54.2±0.96 µm) when compared to LBY4 (45.4±0.96 µm). There were no line difference in endomysium spacing while perimysium spacing was higher for HBY4 males. Selection for Percentage 4-day breast yield has impacted the rate and extent of muscle fiber formation in both the LBY4 and HBY4 lines with no negative impact on fiber spacing. The shift in processing age to later ages has exposed issues associated with muscle fiber viability. Selection during the period of muscle hyperplasia may impact growth rate, however the potential benefits of additional satellite cells is still unclear.